Relationship of colic occurences with nutrition, management and work in horses in the Klang Valley, Malaysia - M. Sabri, Muhammad Syazwan; Hashim, Kalthum; Mohd Adzahan, Noraniza (2011)
Colic is one of the most important conditions in horses. At the Universiti Veterinary Hospital (UVH), Universiti Putra Malaysia, 11% of equine cases treated between 2005 and 2009 were colic cases. In this study, questionnaires were distributed to stable managers of 10 selected stables in the Klang Valley, Malaysia. The questionnaires were designed to determine the association between colic incidences and nutrition management and work. The studies showed that the total prevalence of colic was 28.19% where almost half the cases were form one stable. Stable management contributed the highest incidence of colic (50%) of which 74% was seen in horses that had dental rasping. Long working hours was the second most important predisposing factor, while high protein diet can also contribute to the risk of colic in horses. Other factors were the changed in the type of feeds, use of feed brands and the size of the cubes.